Using the Mass Observation Project: A Case Study in the Practice of Reusing Data - Courage, Fiona (Przegląd Socjologii Jakościowej, 2019)
Mass Observation was founded in 1937 to collect subjective, qualitative data on everyday life in Britain, and has continued to record the ordinary and the everyday ever since. Mass Observation’s purpose has always been to make the data it collects available to a range of disciplines to apply their own methodological approaches upon, resulting in data that can be reused within different projects and disciplines. This paper will use Mass Observation as a case study to illustrate how a sociological shift in attitude towards subjective data has played out in the use of a dataset traditionally viewed as a historical archive. I will review how the data itself is used to define and design methods of analysis, examining the epistemological implications of this approach to research design and the new dimension to the researcher-data subject relationship that is introduced. I will conclude by suggesting that research using Mass Observation exemplifies the methodological opportunities and insights that can be gained by adopting a broader, multi-disciplinary research approach to reusing data.